THE MEANING OF LOCAL WISDOM FOR THE PEOPLE OF NAHDLATUL ULAMA IN KEBUMEN - Imam Subarkah (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2017)
Local wisdom has a high value of life and is worth continuing to be explored, developed,and preserved as antithesis or socio-cultural changes and modernization The researchdesign uses Sequential Explanatory, the research population is NU citizens who havestatus as administrators (Branch level, Deputy branch and branch), Teacher and NUAutonomous Agency Management. the first phase of the study concluded that there wasno difference in the mean (mean) perception of NU citizens about the local wisdom of NUKebumen residents seen from F calculated 0.270 <F table (3.30) While the probabilityvalue was 0.767> 0.05, In general the respondents supported the concept the localwisdom of Kebumen NU residents is indicated by the percentage of approval for eachstatement with a range of 71% -100%. The second phase of research deepens quantitativeresearch with the results of the local wisdom of the NU people in Kebumen Regency.